A Comparison of Reorder Point and Kanban Policies for a Single Machine Production System - Yang, Kum Khiong (Institutional Knowledge at Singapore Management University, 1998)
This paper examines two different policies for managing the production of a set of different parts on a single machine. The demands for the parts are uncertain, but have no lumpy order size. The Reorder Point and Kanban policies are tested in a range of environments characterized by different levels of demand variability, setup time requirement and machine utilization. The results show that Kanban requires less inventory than Reorder Point to achieve the same level of customer service. The dominance of Kanban over Reorder Point, however, diminishes as the demand variability, setup time or machine utilization is reduced. The findings also suggest that Kanban is a simpler policy for achieving different levels of customer service.